La morosidad de pensiones alimenticias y su juzgamiento como delito contra la vida de los beneficiarias del derecho de alimentos en el cantón Santa Rosa, periodo Junio 2012-2013. - Miñan Ramírez, Johana Elizabeth (2014)
Has fulfilled one of the specific objectives was to design an appropriate legal reform regarding prison feed for nonpayment in alimony, regulation, prevention, punishment and in particular propose that the amendment does not infringe the rights of the defendant or the benefits.